The Absorption and Transport of Magnolol in Caco-2 Cell Model - 吴安国 曾宝 黄孟秋 李生梅 陈建南 赖小平 (Chinese journal of integrative medicine, 2013)
Objective： To investigate the absorption and transport mechanism of magnolol in Caco-2 cell model. Methods： A human intestinal epithelial cell model Caco-2 cell in vitro cultured was applied to study the absorption and transport of magnolol, the effects of time, donor concentration, P-gp inhibitor verapamil, pH and temperature on the absorption and transport of magnolol were investigated. The determination of magnolol was performed by high performance liquid chromatography, then the values of apparent permeability coefficient （Papp） and Pratio Basolateral-to-Apical （BL-to-AP）/Apical-to-Basolateral （AP-to-BL） were calculated. Results： In Caco-2 cell model, comparing the amounts of transport of AP-to-BL and BL-to-AP, the latter was larger. At the same donor concentration, either the amounts of transport of AP-to-BL or BL-to-AP increased with increase in donor concentration and incubation time. Verapamil could significantly improve the amounts of transport of AP- to-BL. The transport of AP-to-BL and BL-to-AP depended on temperature, and there was no significant effect of pH on the transport of AP-to-BL. Conclusion： Magnolol could be transported through the intestinal mucosa via a passive diffusion mechanism primarily, coexisting with a carrier-mediated transport, at the same time, the efflux mechanism could be involved.